Precise permeability enhancement technique with hydraulic flushing for coal seams with non-uniformly distributed gas - LIU Ting; LIN Baiquan; ZHAO Yang; ZHAI Cheng; ZOU Quanle (Meitan kexue jishu, 2023)
To realize the precise stress relief and permeability enhancement of the coal seam with non-uniformly distributed gas, the criterion and optimization method of key construction parameters of hydraulic flushing was studied by modeling, numerical simulation and field tests. First, the multiphysics coupling model for stress-relieved coal seam was developed and index of optimal coal discharged was analyzed. Then the criterion and determination method of optimal coal discharged was put forward. Finally, the determination map of key construction parameters of hydraulic flushing was drawn, and a precise permeability enhancement technique for coal seam with non-uniformly distributed gas was proposed. The main conclusions are shown as follows: ① for a given gas extraction time, the residual gas content decreases while the residual gas pressure reduces followed by an increase with a rise of coal discharged; ② the criterion of optimal coal discharged includes the constraints of gas extraction reaching standard and minimization of roadway instability risk and construction cost. When the residual gas content and pressure are less than the critical values, it is considered that the gas extraction reaches the standard. On the premise of meeting the standard of extraction, the coal discharged should be reduced as far as possible to ensure the stability of coal roadway and reduce the project cost; ③ The optimal coal discharged decreases with the increase of ground stress, and increases with the increase of cohesion, gas pressure and borehole spacing. For a given coal seam, there is a maximum value of coal discharged and a minimum value of extraction time reaching standard; ④ comprehensively considering the correlation between coal seam gas pressure, coal yield, borehole spacing and extraction time reaching standard, the optimization map of key parameters of hydraulic flushing is drawn. Based on the map, a precise pressure relief and permeability enhancement technology for coal seams with non-uniformly distributed gas is put forward. In this technique, the construction parameters of hydraulic flushing corresponding to various gas occurrence areas can be determined, with the combination of gas occurrence and optimization map of key parameters, realizing the precise permeability enhancement of the coal seams with non-uniformly distributed gas.